2015
DOI: 10.1111/pan.12603
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of severe intraoperative respiratory compliance changes during ophthalmic arterial chemosurgery for retinoblastoma

Abstract: Here, most patients experienced a severe respiratory compliance event during at least one of their procedures. Overall incidence was 29% and was more likely on subsequent procedures. A severe respiratory compliance event at the initial procedure was poorly predictive of its occurrence on subsequent procedures. No morbidity was associated with intraoperative severe respiratory compliance events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Occurrences of serious cardiorespiratory events seemed to be ostium area specific. We showed that all events occurred after the catheter insertion into the ophthalmic artery's ostium, and not when the catheter was in the cavernous segment of the internal carotid artery as previously reported in retrospective studies . However, the trigger mechanism in the ostium was unclear.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Occurrences of serious cardiorespiratory events seemed to be ostium area specific. We showed that all events occurred after the catheter insertion into the ophthalmic artery's ostium, and not when the catheter was in the cavernous segment of the internal carotid artery as previously reported in retrospective studies . However, the trigger mechanism in the ostium was unclear.…”
Section: Discussionsupporting
confidence: 64%
“…Three retrospective studies report serious adverse cardiorespiratory events during ophthalmic artery chemotherapy including systemic hypotension, bradycardia, and/or respiratory compliance decrease, similar to that observed in acute bronchospasm . The mechanism remains unclear but has been attributed to autonomic reflexes . However, interpretation of these studies is difficult due to their retrospective design, with data collected from heterogeneous anesthesia protocols and endovascular procedures recorded over many years.…”
Section: Introductionmentioning
confidence: 99%
“…Serious adverse cardiorespiratory events including systemic hypotension, bradycardia, and/or respiratory compliance decrease, similar to that observed in acute bronchospasm, is the serious complications during IAC, and its mechanism remains unclear but has been attributed to autonomic reflexes. [ 15 – 17 ] In our patients, 7 cases have bradycardia and hypotension which respond well to intravenous epinephrine bitartrate infusion. The symptom is similar to Klumpp's previous report: [ 18 ] at first, the patients end-tidal CO 2 suddenly decreased and airway resistance increased, followed by a subsequent deterioration in the oxygen saturation.…”
Section: Discussionmentioning
confidence: 83%
“…The pathophysiologic mechanism of these complications is currently unknown, likely involving an autonomic reflex. 22 Most interesting, neither the cardiac and respiratory complications nor the embolic events ever occurred when patients were treated through the ECA; this finding suggests that this route of drug delivery, though more troublesome, should be considered safer than the OA cannulation. Systemic adverse events, mainly pancytopenia, are also rare, probably due to the cumulative result from previous administration of systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 95%